Real financial market exchange rates and capital flows - Maria Gelman; Axel Jochem; Stefan Reitz (Deutsche Bundesbank, 2013)
Foreign exchange rates and capital movements are expected to be closely related to each other as international capital markets become more and more integrated. To account for this fact we construct an index of real effective exchange rates as a weighted average of cross-country asset price ratios. The empirical analysis reveals that a country's real financial effective exchange rate is cointegrated with net foreign holdings of its assets. Comparing the empirical performance of the new index with a standard effective exchange rate deflated by goods prices we find that only the former exhibits an influence on the international flow of capital.
Keywords: F31; G15; E58; 330; Real Effective Exchange Rate; Capital Flows; Financial Markets